2014
DOI: 10.1002/j.1532-2149.2013.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity‐dependent inhibition of spinal wide‐dynamic range neurons by dorsal column and peripheral nerve stimulation in a rat model of neuropathic pain

Abstract: Background Spinal cord stimulation (SCS) and peripheral nerve stimulation (PNS) are thought to reduce pain by activating a sufficient number of large myelinated (Aβ) fibres, which in turn initiate spinal segmental mechanisms of analgesia. However, the volume of neuronal activity and how this activity is associated with different treatment targets is unclear under neuropathic pain conditions. Methods We sought to delineate the intensity-dependent mechanisms of SCS and PNS analgesia by in vivo extracellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…We took advantage of the SNL model, an established surgical model of neuropathic pain that has been used in previous studies to demonstrate the analgesic properties of neurostimulation therapy [17,43,52,54]. We found that 50 Hz Aβ-ES gradually reduced the 1 st amplitudes of C-fiber eEPSC in mice at 1–2 weeks after SNL (n=11).…”
Section: Resultsmentioning
confidence: 99%
“…We took advantage of the SNL model, an established surgical model of neuropathic pain that has been used in previous studies to demonstrate the analgesic properties of neurostimulation therapy [17,43,52,54]. We found that 50 Hz Aβ-ES gradually reduced the 1 st amplitudes of C-fiber eEPSC in mice at 1–2 weeks after SNL (n=11).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that CS at the dorsal column and peripheral nerve inhibit WDR neurons in an intensity-dependent manner (18, 23). Different patterns of CS at moderate stimulus intensity induced significant inhibition of WDR neuronal activity, including windup, in SNL rats.…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of WDR neuronal activity by dorsal column stimulation may partially contribute to SCS-induced analgesia (16, 17, 20, 27). The current study shows that DREZ stimulation with SCS-like parameters also inhibits WDR neurons as dorsal column stimulation does.…”
Section: Discussionmentioning
confidence: 99%